Effect of antepartum meconium staining on perinatal and neonatal outcomes among pregnancies with gastroschisis. (2nd August 2016) - Girsen, Anna I.; Wallenstein, Matthew B.; Davis, Alexis S.; Hintz, Susan R.; Desai, Arti K.; Mansour, Trina; Merritt, T. Allen; Druzin, Maurice L.; Oshiro, Bryan T.; Blumenfeld, Yair J.
Abstract: Objective : To investigate the association between meconium staining and perinatal and neonatal outcomes in pregnancies with gastroschisis. Methods : Retrospective analysis of infants with prenatally diagnosed gastroschisis born in two academic medical centers between 2008 and 2013. Neonatal outcomes of deliveries with and without meconium staining were compared. Primary outcome was defined as any of the following: neonatal sepsis, prolonged mechanical ventilation, bowel atresia or death. Secondary outcomes were preterm delivery, preterm-premature rupture of membranes (PPROM) and prolonged hospital length of stay. Results : One hundred and eight infants with gastroschisis were included of which 56 (52%) had meconium staining at delivery. Infants with meconium staining had a lower gestational age at delivery (36.3 (±1.4) versus 37.0 (±1.2) weeks, p  = 0.007), and a higher rate of PPROM (25% versus 8%, p  = 0.03) than infants without meconium. Meconium staining was not significantly associated with the primary composite outcome or with any of its components. After adjustments, meconium staining remained significantly associated with preterm delivery at <36 weeks [odds ratio OR = 4.0, 95% confidence intervals (CI): 1.5–11.4] and PPROM (OR = 3.8, 95%CI: 1.2–14.5). Conclusions : Among infants with gastroschisis, meconium staining was associated with prematurity and PPROM. No significant increase in other adverse neonatal outcomes was seen among infants with meconium staining, suggesting a limited prognostic value of this finding.